Motional activity as a part of the content of education in the institution of higher education - Voronetskiy, V. B. (Journal of Education, Health and Sport, 2015)
The information of the documentary materials and scientific literature about the state of the on the issue of the terms "motional activity" and "physical activity" was analyzed. The absence of unanimous position concerning the necessity of justification of the position on these categories in the case studies in this direction was found. At the same time it was found that the term "motional activity" should be used to describe the complex characteristics of the individual in need of development. This occurs in the course of physical activity – activity based on physical exercises in various forms.